Supply Chain and Sustainable Fisheries Development of Portable Inflated Solar Power Cold Storage House Technology in Indonesia, Bibliometric Analysis - Setiawan, Muhammad Ikhsan; Abdullah, Dahlan; Lestari, Veronika Nugraheni Sri; Yuniningsih, Yuniningsih (International Journal of Supply Chain Management, 2019)
Based on Scopus Analyze search results and VOS Viewer analysis of supply chain and fisheries research, the development of the portable inflated solar power cold storage house technology is on the right track for the future research and publication in Indonesia. The future research and publication of supply chain and fisheries research in Indonesia are increasing. The country ranks eighth in the supply chain and fisheries research from 1947 to 2019, ranks sixth and twenty-first in the fisheries research from 2019 to 2020 and from 1851-2020, respectively. Universitas Gajah Mada, Universitas Padjadjaran, Universitas Diponegoro, and Institut Pertanian Bogor are dominant universities in the field. Indonesia must increase sponsorship as the source of funding, especially in the development of the portable inflated solar power cold storage house technology, for better and sustainable development of the fisheries.